2020
DOI: 10.3389/fmicb.2020.593056
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Montmorillonite Improves the Intestinal Mucosal Barrier and Optimizes the Intestinal Microbial Community of Weaned Piglets

Abstract: The study investigated the impact of dietary montmorillonite on the growth performance, intestinal mucosal barrier, and microbial community in weaned piglets with control group (CON) and dietary supplementation of 0.2% montmorillonite (0.2% M). Compared with the CON group, 0.2% M feed in the diet increased the average daily gain (ADG) on days 15–35 and day 1–35 and the average daily feed intake on days 1–35 (ADFI) (0.05 < P < 0.1). Besides, higher villus height of the duodenum and jejunum and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Clearly, the supplementation of MMT affected the dominant microbiota. Other studies have showed similar results that dietary MMT can help to maintain gut health by promoting the growth of beneficial bacteria [ 42 ].…”
Section: Discussionmentioning
confidence: 57%
“…Clearly, the supplementation of MMT affected the dominant microbiota. Other studies have showed similar results that dietary MMT can help to maintain gut health by promoting the growth of beneficial bacteria [ 42 ].…”
Section: Discussionmentioning
confidence: 57%
“…In the present research, ZnO and C_ZnO both elevated the villus height in the foregut, which broadened the intestinal absorption surface area. However, there was no significant difference in crypt depth, which commonly reflected the rate of intestinal renewal and secretion function (22), and the index reflected absorption capacity, the ratio of villus height to crypt depth, was not affected either.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, based on aforementioned mechanisms, dietary PAL would improve intestinal morphological characteristics through the promotion of mucosal antioxidant status and immunity, or the relief from oxidative stress and inflammatory response. A similar study conducted in broilers revealed that the better mucosal morphology by montmorillonite contributed to the increased nutrient digestibility as well as intestinal defense function, which may be relate to the improvement of the intestinal microecological environment (Liu H. et al, 2020 ). Besides, the shorter villi in birds fed ANT diet may also be correlated with the alteration of bacteria populations (Baurhoo et al, 2007 ).…”
Section: Discussionmentioning
confidence: 87%
“…Clay minerals have been considered as promising alternatives to AGPs, due to their specific structures, as well as special physical and chemical properties (Gadde et al, 2017 ). Some clay minerals were proposed and tested in animals to improve health status and production performance, such as bentonite (Attar et al, 2018 ), montmorillonite (Liu H. et al, 2020 ) and zeolite (Qu et al, 2019 ). Palygorskite (PAL), also known as attapulgite, is a kind of hydrated magnesium aluminum silicate with ribbons of 2:1 phyllosilicate unit, possessing rod-shaped crystals, plentiful pores, and active silanol groups, which in turn endow it with particular characteristics (Murray, 2000 ; McKeown et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%